Pengaruh Kepuasan Dan Persepsi Kualitas Terhadap Loyalitas Pelanggan Pada Toko Yuikaashop Kabupaten Bima - ST. Farida; Ismunandar Ismunandar (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Every day the fashion business is increasingly in demand by entrepreneurs, both new and experienced. When building a fashion store, you must think about consumer satisfaction and product quality because satisfied customers tend to create profitable relationships to create customer loyalty. Consumer satisfaction and good product quality are determining factors for the success of a business, especially the fashion business. Companies must think about product satisfaction and quality first so that the business they undertake becomes a success. Consumer satisfaction is defined as an effort to fulfill something or make something adequate. Basically, consumer satisfaction is a condition where consumer needs, desires and expectations can be met through the services or products consumed. According to Oliver (2019) satisfaction is the level of a person's feelings after comparing their perceived performance/results with expectations, so the level of satisfaction is a function of the difference between perceived performance and expectations, if it does not match expectations then the customer will be disappointed. If performance meets expectations, consumers will be very satisfied, whereas if performance exceeds expectations, customers will be very satisfied.